Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Kinerja Keuangan PT. Semen Indonesia (Persero) Tbk - Irza Fiyan Anggara; Erry Andhaniwati (Universitas Batanghari Jambi, 2023)
This study aims to investigate the effect of Liquidity, Leverage, and Profitability on the Financial Performance of PT. Semen Indonesia (Persero) Tbk 2013-2021. The secondary data source is in the form of the annual financial report of PT. Semen Indonesia (Persero) Tbk. This type of research uses quantitative. The data analysis technique is in the form of a Partial Least Square (PLS) approach with the SmartPLS Ver 4 Software tool. The results of the study prove that (1) Liquidity has a negative and insignificant effect on the Financial Performance of PT. Semen Indonesia (Persero) Tbk in 2013-2021, (2) Leverage has a positive and insignificant effect on the Financial Performance of PT. Semen Indonesia (Persero) Tbk in 2013-2021, (3) Profitability has a positive and insignificant effect on the Financial Performance of PT. Semen Indonesia (Persero) Tbk 2013-2021